Dentigerous cyst with an impacted third molar obliterating complete maxillary sinus - Sanjay Asnani; Uma Mahindra; B M Rudagi; Yogesh Kini; Viraj R Kharkar (Wolters Kluwer Medknow Publications, 2012)
Dentigerous cyst is the most commonly occurring odontogenic cyst after radicular cyst and accounts for 15% of all true cysts in the jaws. The cyst is more common in mandible than in maxilla. The dentigerous cyst is commonly associated with impacted mandibular third molars. In maxilla, the incidence is rare. Dentigerous cyst in maxillary sinus in association with an impacted third molar is an uncommon entity. We present a case of dentigerous cyst associated with an impacted third molar, completely obliterating the maxillary sinus in a 28-year-old female.